Strategi Guru TK Aisyiyah dalam Menghadapi Keberagaman Karakter Anak Usia Dini di Wilayah Jebres Kota Surakarta - Viony Rahmawati Jubaidah; Faqih Purnomosidi; Anniez Rachmawati Musslifah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This study aims to analyze the strategies used by kindergarten teachers in dealing with the diversity of young children’s characters in the classroom. The research was conducted at TK Aisyiyah X Surakarta using a descriptive qualitative method through interviews, observations, and documentation. The informants consisted of five classroom teachers and two parents. The results show that teachers apply various strategies, including individual approaches, the use of play-based media, and positive behavior habituation. These strategies cover five main aspects: creating an inclusive learning environment, personalized learning, positive reinforcement, behavioral observation, and independent practice. The implementation of these strategies helps teachers foster values of tolerance, cooperation, empathy, and independence among children while creating a supportive and inclusive learning atmosphere. Teachers are expected to continue developing creative strategies and collaborate with parents to support children’s character development effectively.